Contrastive Analysis Between English Medical Terms with Affixes and Their Indonesian Equivalent in Dorland’s Illustrated Medical Dictionary - Nur Indah Sulistyowati Lutfiyah; Jumanto Jumanto (Journal of linguistics, culture and communication, 2023)
Medical terms are language units used to describe medical conditions such as diseases, symptoms, anatomy, and procedures. Medical terms are composed of a combination of affixes and root words. This research focused on contrastive analysis, a study comparing two languages, the source language and their equivalent in the target language. This study aims (1) to find out similarities between English medical terms with affixes in English and their Indonesian equivalents in Dorland's Illustrated Medical Dictionary (2) to find out differences between English medical terms with affixes in English and their Indonesian equivalents in Dorland's Illustrated Medical Dictionary (3) to predict learning problems based on the differences between English medical terms with affixes in English and their Indonesian equivalents in Dorland's Illustrated Medical Dictionary. The data source of this research is "Dorland's Illustrated Medical Dictionary 31st edition" by W.A. Newman Dorland and translated into Indonesian under the title " Kamus Kedokteran Dorland Edisi 3" by Retna Neary Elseria et al. This research is qualitative, and the type of research is library research. The study's results revealed seven affix English medical terms that have similarities with Indonesian equivalents and 93 terms that differ from Indonesian equivalents. The similarities and differences are divided into prefixes and suffixes. There are 8 types of prefixes and 4 types of suffixes. Predictions of problems that may occur in these conditions are in different forms, uses, and meanings. This research is expected to help better understand affixes in English medical terms and their Indonesian equivalents.